2022
DOI: 10.1177/00031348221142590
|View full text |Cite
|
Sign up to set email alerts
|

Early Ambulation is Associated with Improved Outcomes Following Colorectal Surgery

Abstract: Background The Enhanced Recovery After Surgery (ERAS) society lists early mobilization as one of their recommendations for improving patient outcomes following colorectal surgery. The level of supporting evidence, however, is relatively weak, and furthermore, the ERAS guidelines do not clearly define “early” mobilization. In this study, we define mobilization in terms of time to first ambulation after surgery and develop an outcome-based cutoff for early mobilization. Methods This is a retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In this study, early ambulation was found to be independently associated with early discharge. A similar finding has been found in a study in patients after colorectal surgery in whom failure to mobilize within 24 h of surgery was associated with an increase in adverse outcomes from 22% to 36% 23 . We noted a two‐fold increase in the number of patients achieving ambulation in the corridor on PoD 1 between the two groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, early ambulation was found to be independently associated with early discharge. A similar finding has been found in a study in patients after colorectal surgery in whom failure to mobilize within 24 h of surgery was associated with an increase in adverse outcomes from 22% to 36% 23 . We noted a two‐fold increase in the number of patients achieving ambulation in the corridor on PoD 1 between the two groups.…”
Section: Discussionsupporting
confidence: 90%
“…A similar finding has been found in a study in patients after colorectal surgery in whom failure to mobilize within 24 h of surgery was associated with an increase in adverse outcomes from 22% to 36%. 23 We noted a two-fold increase in the number of patients achieving ambulation in the corridor on PoD 1 between the two groups. This result is likely multifactorial, reflecting improvement in physiotherapy, multimodal analgesia with avoidance of intravenous opioids, and ward nursing staff awareness toward the goals of ERAS.…”
Section: Discussionmentioning
confidence: 64%
“… 24 was identified as the study with the lowest quality (score 14/28). Common methodologic issues observed in the included studies were strong reporting data on adverse events due to intervention 15 , 18 , 26 , ensuring external validity 7 , 22 , 23 , 26 , 27 , blinding study subjects to the intervention as well as blinding those measuring the outcome parameters 17 , ensuring concealment of allocation 7 , 17–19 , 22 , 23 , 27 , 28 and providing information on statistical power 14 , 17 , 19–22 , 25 , 27 , 28 . Relevant characteristics and variables of the intervention and control subgroups in retrospective studies were further extracted for comparison ( Table S3 , Supplementary material ).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas most studies listed standard surgical and non-surgical complications (within 30 days) graded in accordance with the Clavien–Dindo classification (CDC), three studies concentrated on defined postoperative pulmonary complications (PPC) only 15 , 18 , 26 . The three studies with the largest number of included patients ( n = 291–1170) were retrospective and described a significantly lower complication rate in patients with EPM, mainly after colorectal surgery 20 , 24 , 25 . Consequently, a subgroup meta-analysis of morbidity rate after EPM in colorectal patients ( n = 4 studies) 14 , 19 , 20 , 25 resulted in a significant relative risk (RR) reduction in postoperative complications (RR 0.60 (0.47, 0.77), P < 0.01, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Relatively recent studies evaluating the impact of postsurgical pain of physical function have emphasized the functional importance of movement-evoked pain. 26,27 Furthermore, early and improved postoperative mobilization has been associated with accelerated physiologic recovery and fewer postoperative complications, 28–31 and such mobilization is greatly facilitated by treatment-induced reductions in movement-evoked pain. Among the trials included in our review that assessed movement-evoked pain as a pain outcome, the choice of a pain-evoking maneuver ( e.g.…”
Section: Discussionmentioning
confidence: 99%